2014
DOI: 10.1186/1471-2318-14-116
|View full text |Cite
|
Sign up to set email alerts
|

Opti-Med: the effectiveness of optimised clinical medication reviews in older people with ‘geriatric giants’ in general practice; study protocol of a cluster randomised controlled trial

Abstract: BackgroundInappropriate drug use has been identified as one of the most important problems affecting the quality of care in older people. Inappropriate drug use may increase the risk of the occurrence of ‘geriatric giants’ such as immobility, instability, incontinence and cognitive impairment. There are indications that clinical medication reviews (CMR) can reduce inappropriate drug use. However, CMRs have not yet been implemented at a large scale in primary care. An innovative medication review program in pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…Also, in noncardiovascular patients most RCTs with an overall medication review as the single intervention showed a positive effect on the number of DRPs . Although the mean number of drugs used by the intervention patients in these studies is comparable to our study (range 6–10 drugs/patient), the mean number of potential DRPs (range 4.4–8.6 potential DRPs/patient) and the mean number of actual DRPs/proposals for intervention per patient (range 1–6 per patient) reported in these studies with noncardiovascular patients were generally higher . There are several possible explanations for this difference in findings.…”
Section: Discussionsupporting
confidence: 49%
“…Also, in noncardiovascular patients most RCTs with an overall medication review as the single intervention showed a positive effect on the number of DRPs . Although the mean number of drugs used by the intervention patients in these studies is comparable to our study (range 6–10 drugs/patient), the mean number of potential DRPs (range 4.4–8.6 potential DRPs/patient) and the mean number of actual DRPs/proposals for intervention per patient (range 1–6 per patient) reported in these studies with noncardiovascular patients were generally higher . There are several possible explanations for this difference in findings.…”
Section: Discussionsupporting
confidence: 49%
“…Other studies concerning improving appropriate prescription in (mostly older) patients receiving complex polypharmacy present a more time-consuming algorithm or method than usual care [ 26 ]. The time aspect might be a strength of our approach in comparison to other ongoing studies [ 14 , 15 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on other studies [ 24 ], measurements of EQ-5D-3 L might even enable an economic evaluation of the danger of adverse drug reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The Dutch guideline for polypharmacy in older patients recommends face-to-face interviews, however this is very time-consuming. [ 14 , 15 ], Patient involvement in medication reviews is desirable and may improve patient outcomes, but as yet is not evidence-based and might not be needed at all times and costs [ 8 ].…”
Section: Introductionmentioning
confidence: 99%